Evaluation of the functional condition of patients qualified for the treatment of hip alloplasty - Padewski, Rafał; Szczypiór-Piasecka, Karina; Antczak, Krzysztof; Mińko, Alicja (Journal of Education, Health and Sport, 2021)
Introduction: Osteoarthritis of the hip joint is one of the most popular diseases affecting this joint. It most often occurs in people aged 50-80 years, but there is a risk of its occurrence in younger people due to predisposing factors. Changes in the joint are irreversible and the only way to stop the progressive changes is properly selected rehabilitation and, at a later stage, performing hip arthroplasty. The scope of physiotherapy includes areas such as kinesiotherapy, physical therapy, manual therapy and osteopathy. Aim: 1.To assess the clinical and functional condition of patients prior to hip arthroplasty. 2.Determination of factors influencing the increase in lower limb dysfunction. 3.Assessment of pain in osteoarthritis of the hip joint. Materials and methods: 46 people qualified for hip arthroplasty took part in the study. The study included the assessment of the range of motion using an inclinometer, the assessment of muscle strength according to the Lovett scale and the assessment of pain using the VAS scale. Results: In the study group, the greatest changes were observed in the reduction of the range of flexion mobility (p <0.05) and the internal rotation movement (p <0.05). There was a reduction in the range of mobility of extension, abduction, adduction and external rotation, but the results were not statistically significant. Degenerative changes predispose to increased pain (p <0.05). The patient’s muscular strength decreases with the severity of the degenerative changes (p <0.05). Increasing pain causes the weakening of muscle strength (p <0.05). Conclusions: 1.Patients with coxarthrosis are characterized by a reduced range of motion in all motor planes, in particular flexion and internal rotation. 2.Degenerative changes reduce the muscle strength of the hip joint. 3.Pain increases along with the advancement of osteoarthritis.